Biological corridors are crucial habitat features that boost biodiversity in agroecological systems of Argentina - Taraborelli, Paula Andrea (2026)
The implementation of biological corridors in agroecosystems is a management strategy to increase biodiversity and create habitats for beneficial species that help reestablish biological and natural control by improving the complexity of trophic networks and the provision of additional ecosystem services. Our aim is to ascertain and contrast the agrobiodiversity, ecological indicators and associated trophic interactions of the arthropod populations, birds, mammals and vegetation in two crops in an agroecological field and different types of biological corridors measured in 2022 in the south-central region of Buenos Aires province, Argentina. Comparing the shrub-herbaceous corridor to the agroecological crops, the former had the maximum richness, density of individuals/ha and Shannon diversity index; the latter was observed in the tree-herbaceous corridor. This one has the highest number of interactions, level of grouping and Agro Index. This suggests that there are more self-regulating mechanisms and more cohesiveness and integration among the system's constituent parts. The percentage of beneficial species in the shrub-herbaceous corridor and in the natural corridor was highest. Therefore, biological corridors in productive systems are a strategy that promotes the maintenance of health in agroecosystems, since they can provide resources and shelter habitat for beneficial insects, wild species (insectivorous and carnivorous birds) and thereby enhance the natural control of problem species. By increasing the interactions with the surrounding environment through biodiversity within productive systems, the use of native plants in biological corridors would allow the generation of more harmonious habitats. Practical implication. Our work shows for the first time in the region that biological corridors increase biodiversity and promote interactions between different components of the production system, using a methodology never before used in Argentina such as the Griffon index. This study provides precise and understandable information for technicians, producers and legislators on the effects, accurate and comprehensible information on the costs and effects of the integrating of biological elements in various production systems, which facilitates the adoption and promotion of the benefits of the inclusion of the practice in agroecosystems.